2020
DOI: 10.1002/cbin.11455
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol‐conjugated bovine serum albumin nanoparticles as a tamoxifen tumor‐targeted delivery system

Abstract: In the present study, we introduced cholesterol (CLO)‐conjugated bovine serum albumin nanoparticles (BSA NPs) as a new system for indirect targeting drug delivery. Tamoxifen, as an anticancer drug, was loaded on BSA NPs (BSA‐TAX NPs); CLO was then conjugated to the BSA‐TAX NPs surface for the targeted delivery of NPs system, by 1‐ethyl‐3‐(3‐dimethylaminopropyl) carbodiimide/N‐hydroxy succinimide carbodiimide chemistry (CLO‐BSA‐TAX NPs). The physicochemical properties, toxicity, in vitro, and in vivo biocompati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…BSA NPs and BSA‐Ba NPs were synthesized by the modified desolation method. [ 23 ] Briefly, 100 mg BSA was added to 3.5 ml PBS (or 3.5 ml PBS with 0.01% Zn NPs to prepare BSA‐Ba@Zn NPs) and kept at 40–50°C under vigorous stirring for 15 min. Next, 7 ml Ba solution with a concentration of 4 mg ml −1 (Ba/acetone solution) was dropwise added to each of the above solutions under constant stirring and dark conditions.…”
Section: Methodsmentioning
confidence: 99%
“…BSA NPs and BSA‐Ba NPs were synthesized by the modified desolation method. [ 23 ] Briefly, 100 mg BSA was added to 3.5 ml PBS (or 3.5 ml PBS with 0.01% Zn NPs to prepare BSA‐Ba@Zn NPs) and kept at 40–50°C under vigorous stirring for 15 min. Next, 7 ml Ba solution with a concentration of 4 mg ml −1 (Ba/acetone solution) was dropwise added to each of the above solutions under constant stirring and dark conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The hemocompatibility assay data observed that all samples' hemolytic activity (fruit extract, purified SeNPs, and SS) were concentration‐dependent, without significantly increasing hemolytic activity. Hence, it can be concluded the systems have relatively appropriate biocompatibility, which was approved by previous studies (Gharbavi, Johari, Eslami, et al, 2020; Mittal & Banerjee, 2021). Furthermore, these results are consistent with the MTT assay cytotoxicity of the samples (purified SeNPs and SS) against HEK‐293 normal cells and confirmed that the investigated samples are biologically safe, high biocompatibility, and nontoxic for medicinal applications, which was reported by other studies (Mittal & Banerjee, 2021; Xu, 2020; Yan et al, 2020).…”
Section: Discussionmentioning
confidence: 69%
“…All mice were acclimatized in an animal house under standard conditions for 1 week prior to use. In this assay, eight BALB/c male mice at an average weight of 25–30 g were used according to the OECD guidelines. , This assay was carried out at different NISM@B-DEC concentrations (17.5–1750 mg/kg) to determine the maximum nontoxic concentration of NISM@B-DEC to be used. All animals were monitored to observe any behavioral changes or signs of toxicity after oral administration.…”
Section: Methodsmentioning
confidence: 99%